From Criminals to Martyrs: Images of Executions in the Art of the Roman Empire - Panteleev, Aleksey D. (Actual Problems of Theory and History of Art, 2017)
The article analyzes scenes from Roman games with wild animals presented on pottery and mosaics(mainly from North Africa; 1st–5th centuries AD). These images show animal chase (venatio) and public executions of criminals, which were an integral part of these games. Analysing the popularity of these scenes wecome to a conclusion that the highly elaborated mosaics from Zliten or El Djem were focused on glorification of the home owner, who had either organized, or sponsored urban games. It is possible that the images on ceramics initially might also have performed commemorative function, but eventually turned into an independent pictorialtype. Roman love for cruelty was the main reason for the popularity of these images. One should not link vessels with such images, dating from 4th–5th centuries with the cult of martyrs. They still represented execution of criminals, but some illiterate persons could believe that they depicted martyrdom scenes.
Keywords: Roman Empire; pottery; mosaics; death penalty; Roman games; Early Christianity